Role of chaperonin-like proteins in Bardet-Biedl syndrome - Leroux, Michel R. (Henry Stewart Talks, 2007)
Introduction to chaperonins, Evolution of chaperonins, Introduction to Bardet-Biedl syndrome (BBS) and ciliopathies, Cloning of BBS disease genes, Role of chaperonins in Bardet-Biedl syndrome
Reviewed at 2019/11/22